Synthesis and characterization of new second-order NLO chromophores containing the isomeric indolizine moiety for electro-optical materials. (December 2017) - Kalinin, Alexey A.; Smirnov, Maxim A.; Islamova, Liliya N.; Fazleeva, Guzel M.; Vakhonina, Tatyana A.; Levitskaya, Alina I.; Fominykh, Olga D.; Ivanova, Nataliya V.; Khamatgalimov, Ayrat R.; Nizameev, Irek R.; Balakina, Marina Yu.
Abstract: To further explore the potential application of the indolizine donor group in nonlinear optical (NLO) chromophores, we have designed and synthesized new push-pull chromophores( MPI-1)-V-TCF and(MPI-3)-V-TCF, having isomeric 3(1)-methyl-2-phenylindolizin-1(3)-yl (MPI-1(3)) electron donor and TCF acceptor, and compared them with dimethyl aniline (DMA) analogues. The Uv-Vis (linear optical) properties and solvatochromic behavior were also investigated; theoretical predictions of molecular NLO characteristics were done on the basis of the DFT calculations. The indolizine-based chromophores have high thermal stability: the decomposition temperature is 348 °C for(MPI-1)-V-TCF and 343 °C for the(MPI-3)-V-TCF, which is by 10–15 °C higher than that for the chromophoreDMA-V-TCF . An important role is played by the bulky phenyl group, which prevents the aggregation of chromophores in guest-host doped polymer films. In NLO activities, the doped(MPI-1)-V-TCF/PMMA and(MPI-3)-V-TCF/PMMA films display the NLO coefficient, d 33, values of 40 and 42 pm/V, correspondingly, at the chromophore load of 20 wt%. Graphical abstract: (MPI-1)-V-TCF/PMMA and(MPI-3)-V-TCF/PMMA materials with indolizine-based chromophores exhibited nonlinear optical coefficients of about 40 pm/V. Highlights: NLO push-pull isomeric indolizine-based chromophores are designed and synthesized. Photophysical and thermal properties are studied. Quantum-chemical predictions of molecular NLO characteristics are determined. NLO coefficients of guest-host materials are measured.